Ceramide-induced autophagy: To junk or to protect cells? - Pattingre, Sophie (2009)
Ceramide is a sphingolipid bioactive molecule that induces apoptosis and other forms of cell death, and triggers macroautophagy (referred to below as autophagy). Like amino acid starvation, ceramide triggers autophagy by interfering with the mTOR-signaling pathway, and by dissociating the Beclin 1:Bcl-2 complex in a c-Jun N-terminal kinase 1 (JNK1)-mediated Bcl-2 phosphorylation-dependent manner. Dissociation of the Beclin 1:Bcl-2 complex, and the subsequent stimulation of autophagy have been observed in various contexts in which the cellular level of long-chain ceramides was increased. It is notable that the conversion of short-chain ceramides (C(2)-ceramide and C(6)-ceramide) into long-chain ceramide via the activity of ceramide synthase is required to trigger autophagy. The dissociation of the Beclin 1:Bcl-2 complex has also been observed in response to tamoxifen and PDMP (an inhibitor of the enzyme that converts ceramide to glucosylceramide), drugs that increase the intracellular level of long-chain ceramides. However, and in contrast to starvation, over-expression of Bcl-2 does not blunt ceramide-induced autophagy. Whether this autophagy that is unchecked by forced dissociation of the Beclin 1:Bcl-2 complex is related to the ability of ceramide to trigger cell death remains an open question. More generally, the question of whether ceramide-induced autophagy is a dedicated cell death mechanism deserves closer scrutiny.